Silver oxide pole piece with high oxidation degree as well as preparation method and application of silver oxide pole piece

By mixing the solid alkali powder with silver powder and pressing it into silver sheets, and using the infiltration of the alkali solution and heat release during the transformation process, an oxide silver electrode sheet with high oxidation is formed, which solves the problem of low oxidation of the existing silver oxide sheets and improves the discharge time and capacity of the battery.

CN119581468AActive Publication Date: 2025-03-07WUHAN INSTITUTE OF MARINE ELECTRIC PROPULSION (THE 712TH RESEARCH INSTITUTE OF CHINA STATE SHIPBUILDING CORP LTD)
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411716890.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-07
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

The existing silver oxide sheet has a low oxidation degree, which affects the discharge capacity and internal resistance of the battery.

Method used

By mixing the solid alkali powder with the silver powder evenly, pressing it into silver sheets, and then using the infiltration of the alkali solution and heat release during the transformation process, a high-oxidation silver oxide sheet is formed.

Benefits of technology

The oxidation degree of the silver oxide sheet is improved, the discharge time of the battery is extended, the capacity of the battery is improved, and the process is simple, the cost is low, and it is easy to mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581468A_ABST
    Figure CN119581468A_ABST
Patent Text Reader

Abstract

The invention discloses a high-oxidation-degree silver oxide pole piece and a preparation method and application thereof. The oxidation degree of the high-oxidation-degree silver oxide pole piece is greater than or equal to 85%. The preparation method of the high-oxidation-degree silver oxide pole piece comprises the following steps: uniformly mixing solid alkali powder with silver powder to obtain mixed silver powder; pressing the mixed silver powder into a silver sheet; and forming the silver sheet, and then washing and drying to obtain the high-oxidation-degree silver oxide pole piece. The oxidation degree of the silver oxide pole piece is higher than that of a traditional silver oxide pole piece; the method disclosed by the invention has the advantages of low cost, simple and controllable technological process and easiness in realizing batch production; when the high-oxidation-degree silver oxide electrode is applied to a battery, the discharge time of the battery is prolonged, and the capacity of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrode pole pieces, and in particular to a high-oxidation-degree silver oxide pole piece and a preparation method and application thereof. Background Art

[0002] Silver oxide electrodes have the characteristics of high specific energy and high specific power. They are usually combined with metal anodes such as zinc, cadmium, iron, aluminum or lithium to form primary or secondary batteries. Their electrolytes are generally alkaline aqueous solutions, among which zinc-silver batteries are the most widely used. Zinc-silver batteries were initially used in the field of underwater equipment, and then underwater applications were developed, including underwater submersibles, buoys, special test ships, etc. Zinc-silver batteries also have many space applications such as spacecraft launch, missile control, remote sensing, self-destructive power supplies, etc.

[0003] The composition of the positive active material in the silver oxide electrode is mainly divalent silver oxide AgO and monovalent silver oxide Ag2O. The characteristics of these oxides determine the characteristics of the silver electrode. The specific capacity of AgO (0.43 Ah / g) is nearly twice that of Ag2O (0.23Ah / g). The specific resistance of divalent silver AgO is 10~15Ω·cm, and the specific resistance of Ag2O is about 108Ω·cm. It can be seen that the higher the content of divalent silver oxide AgO in the silver oxide electrode, the higher the discharge capacity of the battery and the smaller the internal resistance of the battery. The mass percentage of divalent silver oxide AgO in the silver oxide electrode is usually expressed by oxidation degree and tested by iodine titration. At present, silver oxide pole pieces are generally prepared by silver powder pressing and chemical formation, and the oxidation degree is about 80%.

[0004] Therefore, it is urgent to optimize the preparation process of silver oxide electrodes to obtain silver oxide electrodes with a high degree of oxidation. Summary of the invention

[0005] The purpose of the present invention is to overcome the above technical deficiencies, propose a high-oxidation silver oxide electrode and its preparation method and application, and solve the technical problem of low oxidation degree of silver oxide electrode in the prior art.

[0006] In a first aspect, the present invention provides a high-oxidation silver oxide electrode, wherein the oxidation degree of the high-oxidation silver oxide electrode is ≥85%.

[0007] In a second aspect, the present invention provides a method for preparing a high-oxidation-degree silver oxide electrode, comprising the following steps: The solid alkali powder and the silver powder are mixed evenly to obtain mixed silver powder; Pressing the mixed silver powder into silver flakes; The silver sheet is chemically processed, and then washed and dried to obtain a high-oxidation-degree silver oxide electrode.

[0008] In a third aspect, the present invention provides the use of the above-mentioned high-oxidation degree silver oxide electrode as a positive electrode of a battery.

[0009] Compared with the prior art, the beneficial effects of the present invention include: The oxidation degree of the silver oxide electrode of the present invention is higher than that of the traditional silver oxide electrode; the method of the present invention has the advantages of low cost, simple and controllable process, and easier mass production; the high-oxidation-degree silver oxide electrode of the present invention is applied to the battery, which prolongs the discharge time of the battery and improves the battery capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 It is a process flow chart of an embodiment of a method for preparing a high-oxidation-degree silver oxide electrode provided by the present invention; Figure 2 It is the discharge curve of the battery assembled with the silver oxide pole pieces prepared in Examples 1-5 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0011] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0012] In a first aspect, the present invention provides a high-oxidation silver oxide electrode, wherein the oxidation degree of the high-oxidation silver oxide electrode is ≥85%, preferably ≥88%.

[0013] See also Figure 1 In a second aspect, the present invention provides a method for preparing a high-oxidation-degree silver oxide electrode, comprising the following steps: S1, mixing solid alkali powder and silver powder evenly to obtain mixed silver powder; S2, pressing the mixed silver powder into silver flakes; S3, chemically converting the silver sheet, and then washing and drying it to obtain a high-oxidation silver oxide electrode.

[0014] The present invention is to press a solid alkali powder and a silver powder into a silver sheet after mixing them evenly, and then chemically convert the silver sheet to obtain a high-oxidation silver oxide electrode. Since the silver sheet is mixed with solid alkali powder, the silver sheet is immersed in an alkali solution during chemical conversion, and the solid alkali powder mixed in the silver sheet gradually dissolves. In terms of microstructure, a continuous micrometer-level three-dimensional pore structure is formed in the silver sheet, which is conducive to the full infiltration of the alkali solution during chemical conversion and charging. At the same time, the dissolution of the solid alkali powder keeps the local alkali concentration of the electrode sheet at a high level. During the dissolution process, a certain amount of heat will be released to increase the temperature of the electrode sheet. The higher alkali concentration and the electrode sheet temperature are both conducive to the oxidation of the silver sheet, and finally a high-oxidation silver oxide electrode sheet is obtained. The method has the advantages of low cost, simple and controllable process, and easy to achieve mass production. The prepared silver oxide electrode sheet has a high oxidation degree, which improves the discharge capacity of the battery.

[0015] In this embodiment, in step S1, the solid alkali powder is at least one of sodium hydroxide, potassium hydroxide, sodium carbonate and potassium carbonate.

[0016] In this embodiment, in step S1, the D50 particle size of the solid alkali powder is 4-15μm, including but not limited to 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, etc. The present invention controls the particle size of the solid alkali powder within the above-mentioned micrometer range, so that the pressed pole piece is convenient to form a micrometer-level three-dimensional pore structure during the formation process due to the dissolution of the solid alkali powder, which is beneficial to the infiltration of the pole piece during the formation process; if the solid alkali powder particles are too large, the internal structure of the pole piece is too loose after the solid alkali powder is dissolved, resulting in low mechanical strength of the pole piece; if the solid alkali powder particles are too small, the pore structure formed after the solid alkali powder is dissolved is small in size, which is not conducive to the infiltration of the pole piece.

[0017] In some specific embodiments of the present invention, in step S1, the solid alkali powder is obtained by crushing and sieving the solid alkali.

[0018] In this embodiment, in step S1, the D50 particle size of the silver powder is 5-100 μm, including but not limited to 5 μm, 10 μm, 15 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, etc. The present invention controls the particle size of the silver powder within this range, which is beneficial to the pressing and formation of the electrode; if the particle size of the silver powder is too high, the specific surface area of ​​the silver powder will be low, which is not conducive to the full reaction of the active material during the formation and electrochemical reaction; if the particle size of the silver powder is too low, the porosity of the electrode (the ratio of the pore volume inside the electrode to the three-dimensional volume of the electrode) will be low, which is not conducive to the electrolyte entering the interior of the electrode during the formation and electrochemical reaction.

[0019] In this embodiment, in step S1, the solid alkali powder accounts for 10%-20% of the mass of the mixed silver powder. The present invention controls the proportion of solid alkali powder within this range, which is conducive to the formation of continuous channels inside the electrode during formation, while not affecting the mechanical strength of the electrode; if the proportion of solid alkali powder is too high, the silver powder structure will be loose, and the silver sheet will lack structural support after the alkali particles are dissolved, and the mechanical strength will be reduced; if the proportion of solid alkali powder is too low, it will result in the inability to form three-dimensional continuous channels inside the electrode after the solid alkali powder is dissolved, and the formation effect is poor.

[0020] In this embodiment, in step S2, the pressing process includes: placing the mixed silver powder and the current collector into a pressing mold, and applying pressure to press them into a silver sheet.

[0021] Among them, the current collector is a silver mesh, and the mesh number of the silver mesh is 5-20 mesh, including but not limited to 5 mesh, 10 mesh, 15 mesh, 20 mesh, etc., and the thickness of the silver mesh is 0.05-0.5mm, including but not limited to 0.05mm, 0.1mm, 0.15mm, 0.2mm, 0.25mm, 0.3mm, 0.35mm, 0.4mm, 0.45mm, 0.5mm, etc.

[0022] In this embodiment, in step S2, during the pressing process, the molding pressure is 5-20MPa, including but not limited to 5MPa, 7MPa, 9MPa, 11MPa, 13MPa, 15MPa, 17MPa, 19MPa, 20MPa, etc.; the holding time is 1-10s, including but not limited to 1s, 3s, 5s, 7s, 9s, 10s, etc.

[0023] In this embodiment, in step S2, the thickness of the silver sheet is 0.5-2.5 mm, including but not limited to 0.5 mm, 1 mm, 1.5 mm, 2 mm, 2.5 mm, etc.

[0024] In this embodiment, both steps S1 and S2 need to be performed in an environment with a humidity of ≤10%.

[0025] In this embodiment, in step S3, during the formation process, the electrolyte is at least one of a sodium hydroxide solution or a potassium hydroxide solution.

[0026] Furthermore, the concentration of the electrolyte is 1-10 mol / L, including but not limited to 1 mol / L, 2 mol / L, 4 mol / L, 6 mol / L, 8 mol / L, 10 mol / L, etc.

[0027] In this embodiment, in step S3, during the chemical formation process, the auxiliary electrode is a stainless steel sheet.

[0028] In this embodiment, in step S3, during the formation process, the charging current is 0.5-5A, including but not limited to 0.5A, 1A, 2A, 3A, 4A, 5A, etc., and the charging time is 12-72h, including but not limited to 12h, 24h, 36h, 48h, 60h, 72h, etc.

[0029] In some specific embodiments of the present invention, in step S3, during the formation process, the battery is first charged at a current of 2-4A for 8-12h, then charged at a current of 1-2A for 16-20h, and finally charged at a current of 0.5-2A for 22-26h.

[0030] In this embodiment, in step S3, during the formation process, the silver sheet is used as the anode and the auxiliary electrode is used as the cathode, separated by an insulator in the middle, and assembled into a formation battery, which is then charged and formed after the electrolyte is injected.

[0031] In a third aspect, the present invention provides the use of the above-mentioned high-oxidation degree silver oxide electrode as a positive electrode of a battery.

[0032] In this embodiment, the battery includes a zinc-silver battery, a cadmium-silver battery, an iron-silver battery, an aluminum-silver battery or a lithium-silver battery.

[0033] Example 1 The method for preparing a high-oxidation-degree silver oxide electrode provided in this embodiment comprises the following steps: (1) Preparation of micron-sized NaOH powder: In a drying room with a humidity of ≤10%, weigh 500 g of NaOH granular alkali for use. Pour the weighed NaOH granular alkali into a grinder and turn on the grinder for grinding. The final micron-sized NaOH powder alkali has a D50 particle size of 10.9 μm. (2) Mixing micron-grade NaOH powder and silver powder: In a drying room with a humidity of ≤10%, weigh 500 g of the prepared micron-grade NaOH powder and 4.5 kg of silver powder (D50 = 12.8 μm), pour them into a mixer, and mix for 20 min; (3) Silver flake pressing: In a dry room with a humidity of ≤10%, a collecting net (silver net mesh number is 10 mesh, thickness is 0.1 mm) is placed in a pressing mold, 100 g of mixed silver powder is weighed and poured into the pressing mold, the powder is evenly scraped, the cover is covered, the pressure is set to 7 MPa for pressing, and the pressure is maintained for 5 seconds to obtain a silver flake; (4) Silver sheet formation: 10 silver sheet electrodes obtained by molding are connected in series with 10 stainless steel sheets, separated by nylon mesh in the middle, and immersed in 6 mol / L KOH solution. The two ends are connected to positive and negative charging cables respectively, and charged according to the charging program of 3A / 10h+1.5A / 18h+1A / 24h. After charging, they are washed and dried to obtain high-oxidation silver oxide electrodes.

[0034] Example 2 The method for preparing a high-oxidation-degree silver oxide electrode provided in this embodiment comprises the following steps: (1) Preparation of micron-sized NaOH powder: In a drying room with a humidity of ≤10%, weigh 750 g of NaOH granular alkali for use. Pour the weighed NaOH granular alkali into a grinder and turn on the grinder for grinding. The final micron-sized NaOH powder alkali has a D50 particle size of 7.4 μm. (2) Mixing micron-grade NaOH powder and silver powder: In a drying room with a humidity of ≤10%, weigh 750 g of the prepared micron-grade NaOH powder and 4.25 kg of silver powder (D50 = 12.8 μm), pour them into a mixer, and mix for 20 min; (3) Silver flake pressing: In a drying room with a humidity of ≤10%, a collecting net (silver net mesh number is 10 mesh, thickness is 0.1 mm) is placed in a pressing mold, 105.9 g of mixed silver powder is weighed and poured into the pressing mold, the powder is evenly scraped, the cover is covered, the pressure is set to 10 MPa for pressing, and the pressure is maintained for 5 seconds to obtain a silver flake; (4) Silver sheet formation: 10 silver sheet electrodes obtained by molding are connected in series with 10 stainless steel sheets, separated by nylon mesh in the middle, and immersed in 6 mol / L KOH solution. The two ends are connected to positive and negative charging cables respectively, and charged according to the charging program of 3A / 10h+1.5A / 18h+1A / 24h. After charging, they are washed and dried to obtain high-oxidation silver oxide electrodes.

[0035] Example 3 The method for preparing a high-oxidation-degree silver oxide electrode provided in this embodiment comprises the following steps: (1) Preparation of micron-sized NaOH powder: In a drying room with a humidity of ≤10%, weigh 1000 g of NaOH granular alkali for use. Pour the weighed NaOH granular alkali into a grinder, turn on the grinder for grinding, and the final micron-sized NaOH powder alkali has a D50 particle size of 4.9 μm; (2) Mixing micron-grade NaOH powder and silver powder: In a drying room with a humidity of ≤10%, weigh 1000 g of the prepared micron-grade NaOH powder and 4 kg of silver powder (D50 = 12.8 μm), pour them into a mixer, and mix for 20 min; (3) Silver flake pressing: In a dry room with a humidity of ≤10%, a collecting net (silver net mesh number is 10 mesh, thickness is 0.1 mm) is placed in a pressing mold, 112.5 g of mixed silver powder is weighed and poured into the pressing mold, the powder is evenly scraped, the cover is covered, the pressure is set to 13 MPa for pressing, and the pressure is maintained for 5 seconds to obtain a silver flake; (4) Silver sheet formation: 10 silver sheet electrodes obtained by molding are connected in series with 10 stainless steel sheets, separated by nylon mesh in the middle, and immersed in 6 mol / L KOH solution. The two ends are connected to positive and negative charging cables respectively, and charged according to the charging program of 3A / 10h+1.5A / 18h+1A / 24h. After charging, they are washed and dried to obtain high-oxidation silver oxide electrodes.

[0036] Example 4 Compared with Example 1, the only difference is that the proportion of micron-sized NaOH powder to mixed silver powder is 25%. The other specific parameters are the same as those in Example 1.

[0037] Example 5 Compared with Example 1, the only difference is that the D50 particle size of the finally obtained micron-sized NaOH powder is 1.1 μm. The other specific parameters are the same as those in Example 1.

[0038] Comparative Example 1 Compared with Example 1, the only difference is that the silver powder is directly pressed into the electrode and then chemically formed to obtain the silver oxide electrode. The other specific parameters and conditions are the same as those in Example 1.

[0039] Comparative Example 2 Compared with Example 1, the only difference is that the NaOH granules are not crushed but directly mixed with the silver powder, and the mixed silver powder is pressed into the electrode. The other specific parameters and conditions are the same as those in Example 1.

[0040] The results show that the particle size of the uncrushed NaOH granules is 1-10 mm, and they cannot be formed after being mixed with silver powder and pressed.

[0041] Performance Testing: Oxidation degree test: The oxidation degree of the electrode was measured by iodine titration method. The test results are shown in Table 1. Electrochemical performance test: silver oxide electrode was used as positive electrode, zinc sheet of the same shape was used as negative electrode, cotton paper was placed in the middle as separator, and assembled into a single battery in a nylon battery shell. The electrolyte was 6 mol / L KOH solution. Constant current discharge was performed under the current condition of 50A. The discharge curve is shown in Figure 1 , discharge time see Table 1.

[0042] Table 1 Oxidation degree and discharge results of silver oxide electrodes in different embodiments and comparative examples

[0043] Through Table 1 and Figure 1 It can be seen that the oxidation degree of the silver oxide pole pieces prepared in Examples 1-3 is higher than that of the traditional silver oxide pole pieces, and due to the increase in the oxidation degree, the capacity of the positive electrode is also increased accordingly. Under the same discharge conditions, the discharge time of the silver oxide pole pieces in Examples 1-3 is longer than that of the traditional silver oxide pole pieces.

[0044] Compared with Example 1, Comparative Example 1 did not add micron-level NaOH powder alkali, and the oxidation degree and discharge time of the prepared silver oxide electrode were significantly lower than those of the silver oxide electrode in Example 1. The reason is that, in Comparative Example 1, no micron-level NaOH powder alkali was added, and the heat released by the dissolution of micron-level NaOH powder alkali in the mixed silver powder and the higher local alkali concentration produced could not be used to promote the oxidation of the silver sheet during the formation.

[0045] Compared with Example 1, too much micron-level NaOH powder alkali is added in Example 4, and the oxidation degree of the prepared silver oxide electrode is slightly higher than that of the silver oxide electrode in Example 1, but the discharge time is shorter than that of the silver oxide electrode in Example 1. The reason is that due to the high proportion of alkali particles, the internal structure of the silver sheet lacks structural support after the alkali particles are dissolved, and the mechanical strength is reduced. During the discharge process, the electrode with low mechanical strength falls off and breaks due to the immersion in the alkali solution and the chemical reaction, which causes the electrode voltage to fluctuate at the end of the discharge and drop prematurely.

[0046] Compared with Example 1, the D50 particle size of the micron-sized NaOH powder in Example 5 is too small, and the oxidation degree and discharge time of the prepared silver oxide electrode are lower than those of the silver oxide electrode in Example 1. The reason is that the particle size of the NaOH powder is relatively small, and some of the NaOH powder with smaller particle sizes is filled in the gaps between the silver powder particles. After the alkali particles are dissolved in the alkali, the three-dimensional channels formed inside are discontinuous, resulting in poor formation effect, lower oxidation degree than the electrode in Example 1, and shorter discharge time of the single cell than the silver oxide electrode in Example 1.

[0047] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A high-oxidation silver oxide electrode, characterized in that: The oxidation degree of the high-oxidation-degree oxidized silver electrode is ≥85%.

2. A method for preparing a high-oxidation-degree silver oxide electrode as claimed in claim 1, characterized in that: The following steps are involved: The solid alkali powder and the silver powder are mixed evenly to obtain mixed silver powder; Pressing the mixed silver powder into silver flakes; The silver sheet is chemically processed, and then washed and dried to obtain a high-oxidation-degree silver oxide electrode.

3. The method for preparing a high-oxidation-degree silver oxide electrode according to claim 2, characterized in that: The solid alkali powder is at least one of sodium hydroxide, potassium hydroxide, sodium carbonate and potassium carbonate.

4. The method for preparing a high-oxidation-degree silver oxide electrode according to claim 2, characterized in that: The D50 particle size of the solid alkali powder is 4-15 μm.

5. The method for preparing a high-oxidation-degree silver oxide electrode according to claim 2, characterized in that: The D50 particle size of the silver powder is 5-100 μm.

6. The method for preparing a high-oxidation-degree silver oxide electrode according to claim 2, characterized in that: The solid alkali powder accounts for 10%-20% of the mass of the mixed silver powder.

7. The method for preparing a high-oxidation-degree silver oxide electrode according to claim 2, characterized in that: The pressing process includes: placing the mixed silver powder and current collector into a pressing mold, and pressing them into a silver sheet under pressure; wherein, The current collector is a silver mesh, and the mesh number of the silver mesh is 5-20 meshes, and the thickness of the silver mesh is 0.05-0.5 mm; and / or, During the pressing process, the molding pressure is 5-20 MPa and the holding time is 1-10 s; and / or, The thickness of the silver sheet is 0.5-2.5 mm.

8. The method for preparing a high-oxidation-degree silver oxide electrode according to claim 2, characterized in that: During the formation process, the electrolyte is at least one of a sodium hydroxide solution or a potassium hydroxide solution; and / or, The concentration of the electrolyte is 1-10 mol / L; and / or, The auxiliary electrode is a stainless steel sheet.

9. The method for preparing a high-oxidation-degree silver oxide electrode according to claim 2, characterized in that: During the formation process, the charging current is 0.5-5A and the charging time is 12-72h.

10. Use of the highly oxidized silver electrode as claimed in claim 1 as a positive electrode of a battery.

Citation Information

Patent Citations

  • Silver oxide electrode with high utilization rate and preparation method

    CN117525269A

  • Electrochemical capacitor and preparation method thereof

    CN1838352A

  • Silver oxide cell

    JP1984146153A

  • HIGH DENSITY AgO MANUFACTURING METHOD FOR BATTERY

    KR1019800001393B1

  • Silver(II) oxide cell and its manufacture

    US4101719A